Student attrition in Spanish: Perspectives of students and teachers in Jamaica - Salmon, Hazel M. (My University, 1992)
The aims of this study were to: 1) assess students’ and teachers’ perceptions of major factors contributing to students’ decision to terminate their study of Spanish at the end of Grade 9, 2) determine the level of accord between teachers’ and students’ views, 3) examine students’ emerging feelings toward the study of Spanish between Grades 7 and 9, and 4) determine possible gender differences in students’ perceptions and feelings relative to their language learning experience. Questionnaires were administered to a random sample of 184 Grade 10 students (79 boys and 105 girls) from 13 government-aided traditional high schools in Jamaica who were dropouts from an intact Spanish class, and 47 teachers of Spanish from the 13 schools. Data analysis suggested that teachers’ and students’ opinions differed widely relative to the importance ascribed to: (a) the irrelevance of Spanish to the students’ interests, (b) low levels of achievement in Spanish, (c) learning difficulty, (d) lack of student interest, (e) lack of motivation, and (f) poor study habits. The findings suggest that students were consistently developing negative feelings towards Spanish from Grade 7. Girls manifested a much greater sensitivity to achievement and to interpersonal relationships, but the research reveals an overwhelming student rejection of a gender orientation to the study of Spanish favoring either boys or girls.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992
Keywords: language education